Bound by sin - Frank, Jacquelyn (Frank, Jacquelyn. Immortal brothers., 2015)
Cursed to burn and heal night after night, Jaykun, who has never known a life that was not surrounded by war and strife, finds salvation in the arms of a mysterious woman who comes from a different world, one that might prove to be too dangerous for even the strongest of immortal warriors.